Comparison of visual shade matching and photographic shade analysis. Issue 2 (6th February 2022) - Rondón, Luis Felipe; Ramírez, Robert; Pecho, Oscar E.
Abstract: Objective: To compare the performance of a standardized photographic shade analysis (PSA) and visual shade matching (VSM) using two color difference formulas. Materials and Methods: Fifty observers (35 undergraduate and 15 graduate students) evaluated the color of two upper left central incisors (LT—light tooth, and DT—dark tooth). VSM was performed using the VITA 3D Master (3D) shade guide in a controlled clinical environment. For PSA, a cross‐polarized filter and a gray card (Whibal) were used to standardize the photographs taken (target teeth and shade tabs from 3D). From the pictures obtained, the CIELAB coordinates, and color differences ( Δ E ab * and Δ E 00 ) were obtained. The shade tabs selected by two experienced researchers were conducted as part of the pilot study, and finally used as a standard for the analysis. Data were analyzed using descriptive statistics and the chi‐square test ( p  ≤ 0.05). Results: Shade tabs selections of VSM and PSA agreed only for LT. The best "Match" selected by the researchers agreed with data from PSA using Δ E 00 . PSA using Δ E 00 showed higher total percentages of "Match" and higher percentage of agreement among observers. A relationship was found for LT performing the PSA ( p  < 0.05). Conclusions: The performance of the PSA was better than the VSM, but only when the CIEDE2000 color difference formula was used. Therefore, the color difference formulas influenced on the performance of PSA. Finally, the PSA improved the precision of the VSM. Clinical Significance: To use a standardized PSA to improve the VSM and shade communication in clinical esthetic dentistry.